2015
DOI: 10.1016/j.bbrc.2015.04.050
|View full text |Cite
|
Sign up to set email alerts
|

NCYM promotes calpain-mediated Myc-nick production in human MYCN-amplified neuroblastoma cells

Abstract: NCYM is a cis-antisense gene of MYCN and is amplified in human neuroblastomas. High NCYM expression is associated with poor prognoses, and the NCYM protein stabilizes MYCN to promote proliferation of neuroblastoma cells. However, the molecular mechanisms of NCYM in the regulation of cell survival have remained poorly characterized. Here we show that NCYM promotes cleavage of MYCN to produce the anti-apoptotic protein, Myc-nick, both in vitro and in vivo. NCYM and Myc-nick were induced at G2/M phase, and NCYM k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…We had previously shown that several distinct tumor types express high levels of MYC-nick (15,16). Moreover, a recent study reported that MYC-nick expression is associated with survival of neuroblastoma cells (55).…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that several distinct tumor types express high levels of MYC-nick (15,16). Moreover, a recent study reported that MYC-nick expression is associated with survival of neuroblastoma cells (55).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a post-transcriptional mRNA stabilization mechanism has been found for p53 expression due to double-stranding p53 mRNA with the Wrap53 gene mRNA [ 8 ], which might be relevant in many cancers. High expression of the MYCN cis-antisense gene NCYM is associated with poor prognosis in neuroblastoma via promotion of production of anti-apoptotic protein Myc-nick [ 18 ]. Sharing a bidirectional promoter leads to coordination of gene expression levels for BAL/BBAP SAGP, providing optimal interaction of their protein products in chemoresistant, diffuse, large-cell lymphomas [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…(32) Therefore, overexpression of reprogramming factors may contribute to chemoresistance in MYCN-non amplified SH-IN cells, possibly by induction of these stem-cell related genes. (29)(30)(31)(32)35,36) Our present findings indicate that partially reprogrammed NB cells could be a valuable in vitro model for understanding how NB cells maintain plasticity and aggressiveness.…”
Section: Discussionmentioning
confidence: 60%
“…Previous reports suggest that the expression level of MYCN is not associated with poor prognosis in MYCN non‐amplified NBs, while the level of NCYM is associated with poor prognosis . Therefore, overexpression of reprogramming factors may contribute to chemoresistance in MYCN ‐non amplified SH‐IN cells, possibly by induction of these stem‐cell related genes …”
Section: Discussionmentioning
confidence: 97%